Treatment of Diabetic Coma with Continuous Low-dose Infusion of Insulin. Issue 5921 (29th June 1974) - Page, M. McB.; Alberti, K. G. M. M.; Greenwood, R.; Gumaa, K. A.; Hockaday, T. D. R.; Lowy, C.; Nabarro, J. D. N.; Pyke, D. A.; Sönksen, P. H.; Watkins, P. J.; West, T. E. T.
Abstract : Thirty-eight patients in diabetic coma from four different centres were treated with a continuous low-dose intravenous infusion of insulin at an average dose of 7·2 IU/hr. All patients recovered rapidly except for one profoundly shocked patient who died. The mean fall in plasma glucose was 58% four hours after the start of insulin. Blood ketone bodies and plasma free fatty acids showed a similar response. There was no significant difference in plasma glucose response according to severity of acidosis or previous treatment with insulin. Hypokalaemia was uncommon. In the treatment of diabetic coma this technique has proved simple, safe, and effective.